Description of the female of Copestylum tigrinum Ricarte & Hancock in Ricarte et al., 2015 (Diptera, Syrphidae), first record in mainland South America and new larval host plant - Miranda, Gil F. G.; Soares, Matheus M. M.; Fernandes, Daniell R. R.; Rafael, José A. (Zootaxa, 2022)
Larvae of Copestylum tigrinum Ricarte & Hancock in Ricarte et al. 2015 were reared from fallen fruits of Casearia combaymensis Tul. (Salicaceae) collected in the Brazilian Amazon (Amazonas, Brazil). This is the first record of this species in mainland South America and Brazil, and the first record of a fruit of Salicaceae as a food substrate for the larvae of C. tigrinum. The female and its genitalia are described for the first time, the puparium is redescribed and some aspects of the biology of Copestylum are discussed.